(untitled) (Research, Society and Development, 2021)
Objective: to identify the perceptions of teamwork according to professionals in a Neurology Unit. Methods: exploratory study with a qualitative approach. 44 health professionals from the Neurology unit of a public teaching hospital participated. Data collection took place through semi-structured interviews, audio-recorded, from August to November 2017, considering the research question: What do Neurology professionals think and how do they experience teamwork in that scenario? Data analysis followed Content Analysis, thematic modality, and was based on the theoretical framework of the health work process. Results: three thematic categories emerged: Work process agents; Non-material instruments of the work process in Neurology; and Management: coordination and leadership. The thematic categories revealed the professionals’ perceptions about teamwork, as well as its facilitators and obstacles, in the neurology unit. Final Considerations: interprofessional relationships based on complementarity, knowledge exchange, effective articulation, and leadership facilitate teamwork and contribute to the quality of health care.